Two New Pentacyclic Triterpene Saponins from the Leaves of Akebia trifoliata - Qiao-Lin Xu; Jing Wang; Li-Mei Dong; Qiang Zhang; Bi Luo; Yong-Xia Jia; Hong-Feng Wang; Jian-Wen Tan (Molecules, 2016)
Two new pentacyclic triterpene saponins, named akebiaoside K (1) and akebiaoside N (2), were isolated from the leaves of Akebia trifoliata, together with five known triterpenoids 3–7. They were all isolated from the leaves of A. trifoliata for the first time. Their structures were established by spectral and chemical means. Triterpenes 5 and 7 were found to show moderate in vitro cytotoxicity against human tumor A549, HeLa and HepG2 cell lines, with IC50 values ranging from 0.023 to 0.038 mM. Triterpenes 5–7 were further revealed to show significant in vitro α-glucosidase inhibitory activity with IC50 values from 0.040 to 0.220 mM, making them more potent than the reference compound acarbose (IC50 0.409 mM). Meanwhile, no obvious inhibitory effects were observed for the isolated triterpene saponins 1–4 in both bioactivity assays.